Analysis of adhesion factors of the external reinforcement and base surface of the bent concrete element. Issue 5 (June 2020) - Simakov, Oleg; Simakov, Aleksandr
Abstract: The development of reinforcement technology for existing reinforced concrete structures requires more accurate and careful consideration of various reinforcement parameters. Refinement of the calculation theory, coefficients, and the introduction of additional criteria make possible to strength structures with greater efficiency. One of the ways to increase the effectiveness of external reinforcement accounting, in fact, increasing the calculated value of the load-bearing capacity of the reinforced section, is consideration the anchoring of the reinforcement element. Currently used methods for calculating the strength of bent elements take into account the coupling of external reinforcement with the surface of the reinforced element by limiting deformations. At the same time, if it is possible to take into account the anchoring of the external reinforcement, both the calculated and the actual bearing capacity of the reinforced element is increase. There's an analyzes the factors that determine the anchoring of the external reinforcement, which affect the load-bearing capacity of the reinforced normal section of the reinforced concrete element. The analysis is based on previous experimental studies, as well as numerical modeling of the distribution of shear forces. The simulation was performed on a single-span reinforced concrete beam with a hinged support. The numerical simulation took into account the nonlinear nature of the deformation of reinforced concrete (reinforced element), as well as the binding external reinforcement. The work of the outermost reinforcement (carbon fibers) was considered linear, since the graph of deformation of the carbon fiber is almost a straight line before destruction.